Randomized Phase III Trial to Test Accelerated Versus Standard Fractionation in Combination With Concurrent Cisplatin for Head and Neck Carcinomas in the Radiation Therapy Oncology Group 0129 Trial: Long-Term Report of Efficacy and Toxicity - Nguyen-Tan, Phuc Felix (J Clin Oncol, 2014)
PURPOSE: We tested the efficacy and toxicity of cisplatin plus accelerated fractionation with a concomitant boost (AFX-C) versus standard fractionation (SFX) in locally advanced head and neck carcinoma (LA-HNC). PATIENTS AND METHODS: Patients had stage III to IV carcinoma of the oral cavity, oropharynx, hypopharynx, or larynx. Radiation therapy schedules were 70 Gy in 35 fractions over 7 weeks (SFX) or 72 Gy in 42 fractions over 6 weeks (AFX-C). Cisplatin doses were 100 mg/m(2) once every 3 weeks for two (AFX-C) or three (SFX) cycles. Toxicities were scored by using National Cancer Institute Common Toxicity Criteria 2.0 and the Radiation Therapy Oncology Group/European Organisation for Research and Treatment of Cancer criteria. Overall survival (OS) and progression-free survival (PFS) rates were estimated by using the Kaplan-Meier method and were compared by using the one-sided log-rank test. Locoregional failure (LRF) and distant metastasis (DM) rates were estimated by using the cumulative incidence method and Gray's test. RESULTS: In all, 721 of 743 patients were analyzable (361, SFX; 360, AFX-C). At a median follow-up of 7.9 years (range, 0.3 to 10.1 years) for 355 surviving patients, no differences were observed in OS (hazard ratio [HR], 0.96; 95% CI, 0.79 to 1.18; P = .37; 8-year survival, 48% v 48%), PFS (HR, 1.02; 95% CI, 0.84 to 1.24; P = .52; 8-year estimate, 42% v 41%), LRF (HR, 1.08; 95% CI, 0.84 to 1.38; P = .78; 8-year estimate, 37% v 39%), or DM (HR, 0.83; 95% CI, 0.56 to 1.24; P = .16; 8-year estimate, 15% v 13%). For oropharyngeal cancer, p16-positive patients had better OS than p16-negative patients (HR, 0.30; 95% CI, 0.21 to 0.42; P < .001; 8-year survival, 70.9% v 30.2%). There were no statistically significant differences in the grade 3 to 5 acute or late toxicities between the two arms and p-16 status. CONCLUSION: When combined with cisplatin, AFX-C neither improved outcome nor increased late toxicity in patients with LA-HNC. Long-term high survival rates in p16-positive patients with oropharyngeal cancer support the ongoing efforts to explore deintensification.